Signatures of lower respiratory tract microbiome in children with severe community-acquired pneumonia using shotgun metagenomic sequencing - Ting-Yu Yen; Ching Hsu; Ni-Chung Lee; Chao-Szu Wu; Hsin Wang; Kuan-Yi Lee; Chia-Ray Lin; Chun-Yi Lu; Mo-Li Tsai; Tzu-Yu Liu; Che Lin; Chien-Yu Chen; et al. (Journal of Microbiology, Immunology and Infection)
Background: Severe community-acquired pneumonia was associated with high morbidity and mortality in children. However, species-level microbiome of lower airway was sparse, and we used shotgun metagenomic next-generation sequencing to explore microbial signatures. Methods: We conducted a prospective cohort study to recruit children under 18 who required admission to an intensive care unit for community-acquired pneumonia between December 2019 and February 2022. Lower respiratory specimens were collected on admission for shotgun metagenomic sequencing. The children were divided into two groups. Critical cases were patients with respiratory failure requiring endotracheal ventilator support, and severe cases did not require intubation. Signatures of lower respiratory tract microbiome were compared between groups using an exact k-mer matching metagenomic analysis pipeline (Kraken 2) and a metagenome-assembled genomes pipeline (MetaWRAP). Results: Totally 66 children were enrolled, and 27 children were critical cases, and the rest were severe cases. There were significant differences in microbial community structure between different severity groups, and microbial abundance was negatively correlated with disease severity. The results showed that Haemophilus influenzae was more prominent in children who were critical, accompanied with increased expression of intracellular transport, secretion, and vesicle transport genes. Rothia mucilaginosa, Dolosigranulum pigrum, and Prevotella melaninogenica tended to be present in less severe community-acquired pneumonia group. Conclusion: This study demonstrated that significantly different microbial community was associated with severity of community-acquired pneumonia requiring intensive care admission. Species-level shotgun metagenomic sequencing facilitates the exploration of potentially pathogenic or protective microbes and shed the light of probiotic development in lower respiratory tract.